Trust and Governance Mechanism in Indonesian Family Small Medium Sized Enterprises - Kussudyarsana, K (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
The purpose of this study is to examine the connection between trust and governance mechanism. The governance mechanisms in this study are formal and relational governance. Formal governance is associated with the application of a formal contract and administrative control. Relational governance believes that people behavior can be controlled by social elements that result from social interaction. The data collection was obtained through face to face interview with owner-managers of 350 family firms in Indonesia. This study used factoranalysis to validate the construct and hierarchical regression to examine the hypothesis. The moderation testing indicates that trust has moderate relationship between uncertainty and formal governance. The result indicates that in the high trust situation, the impact of uncertainty on formal governance was negatively significant. It means that when people have high trust, firms who transact in uncertain environment have less required formal governance.